2022
DOI: 10.1093/infdis/jiab636
|View full text |Cite
|
Sign up to set email alerts
|

Lung Function Decline in Relation to COVID-19 in the General Population: A Matched Cohort Study With Prepandemic Assessment of Lung Function

Abstract: Objective To quantify the potential decline in dynamic lung volumes following coronavirus disease 2019 (COVID-19) in the general population. Methods A prospective matched cohort study of adult Copenhagen General Population Study (CGPS) participants with a pre-pandemic spirometry available. CGPS individuals with a positive SARS-CoV-2 polymerase chain reaction (PCR) test performed a repeat spirometry, a questionnaire regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 36 publications
0
20
0
1
Order By: Relevance
“…An interesting study used prepandemic lung function tests in SARS-CoV-2-positive individuals and matched controls, and evaluated lung volume decline following asymptomatic to mild COVID-19. The results showed that COVID-19 was associated with an accelerated decline in FEV1 and FVC independent of tobacco smoking [21 ▪▪ ]. Unfortunately, DLco was not available in that study [21 ▪▪ ].…”
Section: Pulmonary Function Findingsmentioning
confidence: 87%
“…An interesting study used prepandemic lung function tests in SARS-CoV-2-positive individuals and matched controls, and evaluated lung volume decline following asymptomatic to mild COVID-19. The results showed that COVID-19 was associated with an accelerated decline in FEV1 and FVC independent of tobacco smoking [21 ▪▪ ]. Unfortunately, DLco was not available in that study [21 ▪▪ ].…”
Section: Pulmonary Function Findingsmentioning
confidence: 87%
“…Restrictive lung function is common in several conditions and diseases including lung and pleural diseases but also obesity, deformities of thorax and neuromuscular disease, and notably, other conditions than lung and pleural (Bradley et al, 2008; Stansbury & Mannino, 2009). In addition, the COVID‐19 pandemic may increase the global prevalence of restrictive lung function due to inflammatory response in the lungs (E. et al, 2021; Iversen et al, 2022; Torres‐Castro et al, 2021). On a population level, prevalence estimates of restrictive lung function using dynamic spirometry, that is, restrictive spirometry pattern (RSP), based on normal forced expiratory volume in a one second (FEV 1 )/forced vital capacity (FVC) (or VC) ratios and decreased FVC (or VC) have yielded results between 6% and 8% in the United States (Ford et al, 2013; Kurth & Hnizdo, 2015), from 5% to 19% in Spain (Scarlata et al, 2008), and in Sweden about 10% (Backman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of The Journal of Infectious Diseases , Iverson et al [ 5 ] begin to address some of the outstanding gaps in our understanding of pulmonary impairment after COVID-19. They leveraged the Copenhagen General Population Study, an ongoing, population-based prospective cohort study of the Danish population residing in the Copenhagen area.…”
mentioning
confidence: 99%
“…To assess the impact of COVID-19 on lung function, Iverson et al [ 5 ] first performed repeated-measures linear mixed-effects modeling to determine the mean yearly change in lung function between those with and without COVID-19. Of note, the mean time between baseline and follow-up spirometry sessions for cases and controls was 6.4 and 8.4 years, respectively (although the earliest baseline visit was in December 2003, 16 years before the COVID-19 pandemic began).…”
mentioning
confidence: 99%
See 1 more Smart Citation